SOBERANIA E FISCALIDADE NO BRASIL INDEPENDENTE: CONCEPÇÕES DA IMPRENSA PAULISTA - Leme, Marisa Saenz (Universidade de São Paulo, Faculdade de Filosofia, Letras e Ciências Humanas, Departamento de História, 2015)
Abstract This article discuss by which set of ideas the so called moderate liberals in the province of São Paulo came to give form to what achieved to be theoretically known as a monopoly on taxation, imperative for the creation of the modern state, even in it's liberal dimension. Empirical data for this analysis are provided by the subjects found in the newspapers published in São Paulo during Brazilian's first kingdom: O Farol Paulistano (1827 to 1831) and O Observador Constitucional (1829 to 1831).

Resumo Neste artigo busca-se compreender o modo pelo qual os liberais moderados paulistas chegaram a formular o que teoricamente veio a se conceituar como monopólio fiscal, impreterível para a constituição do Estado moderno, também em sua dimensão liberal. Para tanto são utilizadas as matérias publicadas na imprensa paulista do 1º Reinado, constituída pelos periódicos O Farol Paulistano (1827 a 1831) e O Observador Constitucional (1829 a 1831).
SOVEREIGNTY AND TAXATION IN INDEPENDENT BRAZIL: CONCEPTS IN THE NEWSPAPERS OF THE SÃO PAULO PROVINCE
Keywords: Liberalism; citizenship; taxation; Liberalismo; cidadania; fiscalidade